Impact of “buy Zimbabwe” campaign on Zimbabwean company performance in the retail sector. - Masocha, Brena (Midlands State University, 2017)
The majority of the Zimbabwean retail companies were in the collapsing mode as indicated by a performance decline of more than 50% over the past ten years. This miserable predicament necessitated the government to craft locally-driven remedies, and one of them was the “Buy Zimbabwe” campaign launched in 2011. This prompted the researcher to assess the impact of the “Buy Zimbabwe” campaign on the performance of the Zimbabwean firms. The study objectives were to establish the impact of “buy Zimbabwe” campaign on demand for local products and factors affecting demand for local products. Furthermore to establish if a company participating in the “buy Zimbabwe” campaign performs better than non-participating firms. An earnings per Share was used in the inter-firm performance comparison between OK Zimbabwe and Powerspeed Electrical. Both companies were picked in Harare Graniteside light-industry since the field research was done at their head offices. OK Zimbabwe stands in the place for companies that are participating in the “Buy Zimbabwe” campaign and Powerspeed Electrical represents the Zimbabwean firms that have not adopted the “Buy Zimbabwe” campaign. The descriptive research design was employed, although the research was both quantitative and qualitative in nature. A combination of quantitative and qualitative approach was employed to seek the performances information from the sample population. Interviews were carried out with key informants in this regard - the managers of both companies. Different literatures were reviewed in order to get informed view points of other authors and researchers about the impact of “buy local” campaigns based on the study’s objectives and research questions. Other authors agreed that buy local campaign contributes to company performance intensively emphasis on sales revenue and output of the company, while others argue against that they have insignificant effect. Primary sources such as questionnaires and interviews in conjunction with secondary sources were employed in data gathering. The study had a target population of 506 respondents which consisted of 500 consumers and 3 managers for OK Zimbabwe, and only 3 managers of Powerspeed Electrical. The researcher employed stratified sampling, purposive sampling and systematic sampling to choose the companies and respondents in this study. However, systematic sampling was utilized on sample size of 50 consumers. The response rates for customers and managers were 86%, 100% respectively and tables, graphs and pie charts were used in data analysis and presentation. The classical linear multiple regression analysis was used to establish and explain the relationship between company performances from the period 2009 to 2014 using time-series data for the selected macroeconomic variables. The results indicated a weak linear relationship between “buy Zimbabwe” campaign and company performance in case of OK Zimbabwe, whereas in case of Powerspeed Electrical there was also weak linear relationship. The results indicates that, “buy Zimbabwe” campaign has little influence on company performances as the regression results indicate other factors that are affecting company’s performances in the current operating environment. No much difference was found between OK Zimbabwe and Powerspeed Electrical. The results also discloses that quality and affordability of the product are the most influential factors affect demand for local products and buy Zimbabwe campaign was regarded as the least factor to be considered by consumers. Results from this study point towards the need to put in place supportive policies for the “buy Zimbabwe” campaign to be effective. Also the Government should enact rules and regulations that represent progressive vision and offer crucial incentives that promote local firms. The recommendations can help Zimbabwe to resuscitate the local industry and to become a middle-class nation by 2025.